Dual-layer ultrathin film optics: II. Experimental studies and designs. (16th February 2015) - Lim, Kim Peng; Wang, Qian
Abstract: This paper presents an experimental study of using dual-layer ultrathin films with a high refractive index and low refractive index to approximate a single-layer thin film with an equivalent intermediate refractive index, which is the basis of the functional graded refractive index thin film stack using dual-layer ultrathin films. Using ion beam deposition, five sets of ultrathin films of titanium dioxide (TiO2 ) and aluminium oxide (Al2 O3 ) are deposited on silicon with different volume fractions and characterized by spectroscopic ellipsometer for the ordinary/extraordinary refractive index and by spectrophotometer for the reflectance. By designing the sequence of TiO2 and Al2 O3 ultrathin films, the measured results show a good agreement between the experiments and simulation of the equivalent birefringent thin film. An application example of using the TiO2 and Al2 O3 dual-layer ultrathin films to approximate a single-layer antireflection coating for silicon is presented.